Penerapan Flipped Classroom Dalam Pembelajaran Kimia Siswa Kelas XI MIPA SMA N 2 Mataram - Dyah Maulidia; Renata Sabila Humaira (Educational Note, 2025)
This study aims to examine the implementation of the flipped classroom learning model in improving the effectiveness of chemistry learning at SMA Negeri 2 Mataram. The flipped classroom model is an innovative approach that reverses the traditional structure of instruction by moving content delivery activities outside the classroom through videos or online modules, allowing classroom time to be used for discussion, problem-solving, and collaborative activities. This research employed a quantitative method with a quasi-experimental design using a pretest-posttest control group approach. The research subjects consisted of two eleventh-grade classes selected purposively, with one serving as the experimental class and the other as the control class. The instruments used included a concept understanding test, a learning motivation questionnaire, and an observation sheet of students’ learning activities. The results showed a significant improvement in chemistry concept understanding among students who learned using the flipped classroom model compared to those in the control class who were taught using conventional methods. In addition, students in the experimental class demonstrated higher learning motivation and more active engagement in the learning process. Based on these findings, the flipped classroom model is recommended as an alternative 21st-century instructional strategy that supports active, independent, and meaningful learning in chemistry subjects. The implications of this study highlight the importance of developing digital learning resources to support the implementation of innovative instructional models in schools.